IMPACT OF LAUGHTER YOGA INTERVENTION ON PULMONARY FUNCTION AMONG ORPHAN SPECIAL CHILDREN - Sharma, Anchal; Singh, Moradhvaj; Gusain, Vijay Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Background: Forced Vital Capacity (FVC) is a critical parameter in assessing respiratory function and overall pulmonary health. Children with disabilities, especially those in orphanages, often face additional health burdens, including compromised lung function due to a sedentary lifestyle and stress. Objective: This study investigates the effectiveness of a structured laughter yoga program in enhancing FVC among orphan special children in Delhi. Methodology: A total of 30 orphan special children (15 boys, 15 girls), aged 8–16 years, participated in a 12-week laughter yoga program conducted five days a week, with session durations increasing from 30 to 60 minutes. FVC was measured at five intervals (week 0, 3, 6, 9, and 12). A Two-Way Mixed-Design Repeated Measures ANOVA and Paired Sample T-Test were used to analyze the data. Results: ANOVA results showed a significant main effect of time on FVC (p < .001, partial η² = .386), indicating consistent improvements across the 12 weeks. The gender effect (p = .687) and Time × Gender interaction (p = .580) were not significant. Paired sample t-tests revealed a significant increase in FVC among boys (p = .026) but not among girls (p = .155). Conclusion: Laughter yoga is an effective intervention to improve pulmonary health, particularly in male orphan children with disabilities. Its accessibility and non-invasive nature make it a valuable addition to therapeutic programs for vulnerable populations.